LOUSE -FLIES (ORNITHOMYINAE, DIPTERA) IN HOLLOW-NESTING BIRDS FROM MOSCOW AND MOSCOW REGION - A. V. Matyuhin (Российский паразитологический журнал, 2019)
Objective of research. The purpose of this paper was to study the species composition of louse-flies (Ornithomyinae, Diptera) in hollow-nesting birds from Moscow and Moscow region. Materials and methods. Material was collected during ornithological investigations in permanent nesting locations of hollow-nesting birds on the territory of Moscow and Moscow region in 1997-2016. Altogether, 5473 birds of 21 species were examined; 817 adult louse-flies of 4 species and 17 puparia of the mentioned species were collected. Results and discussion: In the observation period, 4 species of louse-flies were found in hollow-nesting birds in Moscow and Moscow region. Ornithomyia avicularia (60,37%) and Ornithomyia fringillina (37,21%) are dominating. Ornithomyia chloropus (0,82%) is the northern arctic species, the southern boundary of the range in Europe is at the latitude of South Karelia, and this species occurs in Moscow region mainly in migratory birds (September-October). In the breeding period, this species of louse-flies is not registered in Moscow region. O. avicularia is a large louse-fly, looks like a domestic fly. First adult flies appear in Moscow region at the end of May - middle of June depending on the weather conditions. This louse-fly is found in all bird species until the beginning of November. The peak of fly population falls on July-September depending on the year. The number of adult louse-flies in one bird ranged from one to 11-13 individuals. Puparia were registered from the end of June. O. fringillina is a small fly like drosophila. First adult flies appear in the Moscow region ant the middle of June. This species is being found permanently in all types of birds until the beginning of November. The peak of fly population falls on July-September depending on the year. The number of adult louse-flies in one bird ranged from one to 5-7 individuals. Puparia were registered from the end of July. O. chloropus is a rare species of the fauna of Moscow region; found in migratory northern birds; basically appears in the period of fall migration. Сrataerina pallidа is an obligate parasite of the swift, unable to fly, the wings are reduced; found in birds from May, obviously comes from wintering regions. Native flies appear in July-August.